Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi pada Pra Lansia di Wilayah Kerja UPT Puskesmas Sungai Karias - Fitri Amalina; M. Bahrul Ilmi; Ridha Hayati; Akhmad Fauzan (Jurnal Akademika Baiturrahim Jambi, 2022)
Based on data of the UPT Puskesmas Sungai Karias, it was found that hypertension was ranked first among the ten most common diseases. The purpose of this study was to analyze the association  between knowledge of hypertension, smoking behavior, and the habit of consuming salty foods with the incidence of hypertension in pre-elderly. The design of this study used an analytic survey method with a cross sectional approach. Sampling with Accidental Sampling technique with a sample number of 92 respondents. Methods and measuring tools using interviews with a questionnaire guide, then the data analysis carried out was univariate, bivariate using the chi-square test. From the results of the study, it can be concluded that the incidence of hypertension in pre-elderly is the most with hypertension category of 67 respondents (72.8%). Knowledge about hypertension with sufficient and good knowledge has the same value as many as 28 respondents (28.3%). The most smoking behavior in the category of consuming cigarettes was 64 respondents (69.6%). The habit of consuming salty food was the most in the category of heavy consumption habits of 53 respondents (57.6%). There is a association between knowledge of hypertension, smoking behavior, and habit of consuming salty food with the incidence of hypertension at UPT Puskesmas Sungai Karias with respective values = 0.000 < 0.05. It is hoped that the community, especially the pre-elderly can carry out prevention aspects especially the factors that cause hypertension directly or indirectly